Studies on the relationship between glycolysis, lipogenesis, gluconeogenesis, and pyruvate kinase activity of rat and chicken hepatocytes - Ochs, Raymond S.; Harris, Robert A. (Archives of biochemistry and biophysics, 1978)
Chicken hepatocytes synthesize glucose and fatty acids at rates which are faster than rat hepatocytes. The former also consume exogenous lactate and pyruvate at a much faster rate and, in contrast to rat hepatocytes, do not accumulate large quantities of lactate and pyruvate by aerobic glycolysis. α-Cyano-4-hydroxycinnamate, an inhibitor of pyruvate transport, causes lactate and pyruvate accumulation by chicken hepatocytes. Glucagon and N 6, O 2′-dibutyryl adenosine 3′,5′-monophosphate (dibutyryl cyclic AMP) convert pyruvate kinase (EC 2.7.1.40) of rat hepatocytes to a less active form. This effect explains, in part, inhibition of glycolysis, inhibition of lipogenesis, stimulation of gluconeogenesis, and inhibition of the transfer of reducing equivalents from the mitochondrial compartment to the cytoplasmic compartment by these compounds. In contrast, pyruvate kinase of chicken hepatocytes is refractory to inhibition by glucagon or dibutyryl cyclic AMP. Rat liver is known to have predominantly the type L isozyme of pyruvate kinase and chicken liver predominantly the type K. Thus, only the type L isozyme appears subject to interconversion between active and inactive forms by a cyclic AMP-dependent, phosphorylation-dephos-phorylation mechanism. This explains why the transfer of reducing equivalents from the mitochondrial compartment to the cytoplasmic compartment of chicken hepatocytes is insensitive to cyclic AMP. However, glucagon and dibutyryl cyclic AMP inhibit net glucose utilization, inhibit fatty acid synthesis, inhibit lactate and pyruvate accumulation in the presence of α-cyano-4-hydroxycinnamate, and stimulate gluconeogenesis from lactate and dihydroxyacetone by chicken hepatocytes. Thus, a site of action of cyclic AMP distinct from pyruvate kinase must exist in the glycolytic-gluconeogenic pathway of chicken liver.